2011
DOI: 10.4238/2011.december.20.3
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the tropical tree species Aegiphila sellowiana (Lamiaceae)

Abstract: ABSTRACT. The Tibagi River, located in southern Brazil, is associated with a significant degree of environmental heterogeneity, along its 550 km extension. There is concern about the integrity of this river's ecosystem, as human interference has been increasing. Aegiphila sellowiana (Lamiaceae) is an important pioneer tree species, commonly found near rivers; the fruit is consumed by avifauna. We studied this species along three ecological gradients, comprising the upper, middle, and lower regions of the Tibag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Using random-amplified polymorphic DNA (RAPD) and isoenzyme approaches, Wang et al (2008) reported the low diversity of T. sinensis natural resources in China. Compared with RAPD, ISSR and SRAP have higher reproducibility and are more effective for genetic diversity analyses and germplasm evaluation (Shao et al, 2010;Medri et al, 2011;Niu et al, 2015;Liu et al, 2008Liu et al, , 2015Souza-Sobreira et al, 2015). Using these two marker systems, we studied the genetic diversity and genetic relationships of five T. sinensis populations (100 individuals/sample) representing different climates and geographical locations in China.…”
Section: Introductionmentioning
confidence: 99%
“…Using random-amplified polymorphic DNA (RAPD) and isoenzyme approaches, Wang et al (2008) reported the low diversity of T. sinensis natural resources in China. Compared with RAPD, ISSR and SRAP have higher reproducibility and are more effective for genetic diversity analyses and germplasm evaluation (Shao et al, 2010;Medri et al, 2011;Niu et al, 2015;Liu et al, 2008Liu et al, , 2015Souza-Sobreira et al, 2015). Using these two marker systems, we studied the genetic diversity and genetic relationships of five T. sinensis populations (100 individuals/sample) representing different climates and geographical locations in China.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, geographical proximity between fragments does not necessarily mean genetic proximity. Furthermore, Medri et al (2011) found significant correlation between genetic differentiation and geographic distance among nine subpopulations of the tropical tree species Aegiphila sellowiana (Lauraceae), in Brazil. The number of migrants per generation between forest fragment pairs was overestimated, because some pairs do not exchange genes, owing to the distance between them.…”
Section: Genetic Structure Of Forest Fragmentsmentioning
confidence: 97%
“…Dado que la densidad estomática está claramente afectada por la intensidad luminosa, diversos trabajos han demostrado que bajo condiciones de alta irradiación, la frecuencia de estomas por unidad de área superficial de la hoja es mayor (BJORKMAN;HOLMGREN, 1963;EVANS, 1973;BOARDMAN, 1977;ASHTON;TURNER, 1979;MEDRI;LLERAS, 1980). Rocha et al, (2007) indican que la relación de las medidas de los diámetros medios polares sobre los diámetros medios ecuatoriales de los estomas debe ser utilizada como forma de evaluación de la funcionalidad de los mismos.…”
Section: Consideraciones Finalesunclassified